LEAD, STRONTIUM AND REE DIFFUSION COMPENSATION AND ESTIMATION OF THEIR DIFFUSIVITY IN MINERALS - Zhao Z.F.; Zheng Y.F. (My University, 2001)
Inspection of available experimental diffusion data shows compensation effect which not only occurs in Pb, Sr and REE diffusion in different minerals, but also occurs in the different elements of the same mineral or the same mineral groups. For Pb and REE diffusion, there exist linear correlations between anion porosity and activation energy; while for Sr diffusion, there exist linear correlations between anion porosity and diffusion coefficients at some temperatures. As a measure of atomic packing density in minerals, anion porosity can thus be used to predict element diffusion coefficients. This paper predicts lead, strontium and REE diffusivity in minerals by anion porosity and bi-compensation methods, respectively. The empirical results are consistent with known experimental data and thus applicable to studies of geochemical kinetics.